Integrative review applied to walkability and bus stops on university campuses - Camara , Andreia Jane Leandro; Pfützenreuter, Andréa Holz (Technical and Scientific Journal Green Cities, 2025)
Objective – To analyze the relationship between bus stops and walkability within the national and international scientific literature, through a systematic review. Methodology - Terms, search strings, search dates, inclusion and exclusion criteria, and table organization were defined, including articles from at least the last 10 years in three major research databases: Web of Science, Scopus, and SciELO. Therefore, this is a descriptive and exploratory study, in which 304 articles were found, and 20 of them were analyzed, published between 2014 and 2024. Originality/relevance - The observation of concern with the development of measurement instruments on this topic and their validation for the Brazilian context highlights this lack and the importance of meeting users’ needs in utilizing existing resources to obtain maximum benefits. Results - Evidence indicates that the perception of walkability and the replacement of sedentary time with walking impact autonomy and improvement of frailty, especially in elderly people. Theoretical/Methodological Contributions - The availability of numerous measurement instruments contributes to the diagnosis of this gap and the advancement of public policies focused on this issue (theme),since they also reveal aspects that can encourage the population to use transportation less in general and adopt walking as an active mode of transportation. Social and Environmental Contributions - Reveal aspects that can encourage the population to use transportation less in general or use it more appropriately, in addition to adopting walking as an active mode of transportation.